Essential Oils: Psychophysiological Reaction and Changes in Cognitive Processes - Kurapov, Anton; Kurapova, Iryna; Shokota, Valeriia; Balashevych, Aleksandra (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2021)
This article presents the results of the research of specificity of psychophysiological reactions and changes in the cognitive processes as a result of using ephemeral oils by means of a classical experimental study with the use of a polygraph. Theoretical analysis of scientific publications of recent years on this topic was carried out. The scientific novelty of the research consists in specifying the effects of different types of ephemeral oils, determined by their complex influence – activity or quiescence. The effect of stimulating and sedative essential oils on the processing of cognitive processes and changes in the human body, as well as the effect on these characteristics of the subjective perception of the fragrance. As a result, significant differences in the speed of cognitive processes depending on the type of ether oils and associated psychophysiological reactions were revealed. Specifically, the activation of the nervous system in the inhalation of stimulating oils with a decrease in the speed of thought processes and a decrease in concentration, and the opposite effect in the action of sedative oils.
Keywords: essential oils; cognitive processes; psychophysiological reactions; polygraph